A critical analysis of the impact of the MLI in the determination of corporate residency in South Africa: a synthesis of a hierarchy of factors to used for resolving dual residency under map - Naamdhew, Akira (Department of Finance and Tax, 2026)
South Africa was a signatory to the Multilateral Instrument (“MLI”) on 7 June 2021. South Africa has deposited its ratified, accepted, and approved MLI and list of reservations and notification with the OECD on 30 September 2022. The MLI applies from 1 January 2023 in South Africa. In alignment with the OECD/G20 Inclusive Framework on Base Erosion and Profit Shifting (“BEPS”) Action 6, South Africa has elected to include Article 4(1) of the MLI. Article 4(1) deals with the determination of corporate residency and modifies the existing tie-breaker rule in South Africa's Double Taxation Agreements (“DTAs”) to solving cases of dual residency through a Mutual Agreement Procedure (“MAP”). The MLI's approach of using MAP as a tie-breaker includes a non-exhaustive list of criteria that tax authorities may consider as relevant. This approach lacks clear criteria of factors to resolve dual residency, which may lead to delays, uncertainty, and the risk of double taxation where tax authorities do not reach agreement. This research considers South Africa's domestic tax legislation concerning corporate residency and the application of Article 4(1) of the MLI on its treaty network. The study overlays the South African considerations with the United Kingdom and Mauritius domestic legislation and case law in determining corporate tax residency and how this interacts with the application Article 4(1) of the MLI. The result of this study is a proposed hierarchy of factors for taxpayers and tax authorities to consider when determining corporate residency for MAP purposes in instances of corporate dual residency. The study concludes that while Article 4(1) of the MLI acts as an anti-abuse measure, it imposes challenges that should be managed by tax authorities to maintain the fairness and certainty for taxpayers. Thus, suggesting that tax authorities adopt a structured sequence of criteria to provide certainty for corporate dual residency cases.